Development of a UPLC-MS/MS method for establishing Serra da Estrela cheese’s free amino acids profile - Santos, Andreia O. (2020)
Serra da Estrela Cheese is a high-value and widely appreciated Portuguese cheese, which as as Protected Designation of Origin recognition, being its production legally regulated. The protein of foods, as well as its amino acids composition (namely the essential amino acids), represents a fundamental role on the nutritional and technological value of cheese, influencing greatly its flavour.